Medaka and zebrafish contactin1 mutants as a model for understanding neural circuits for motor coordination. (22nd June 2017) - Takeuchi, Miki; Inoue, Chikako; Goshima, Akiko; Nagao, Yusuke; Shimizu, Koichi; Miyamoto, Hiroki; Shimizu, Takashi; Hashimoto, Hisashi; Yonemura, Shigenobu; Kawahara, Atsuo; Hirata, Yutaka; Yoshida, Masayuki; et al.
Abstract : A spontaneous medaka ro mutant shows abnormal wobbling and rolling swimming behaviors. By positional cloning, we mapped the ro locus to a region containing the gene encoding Contactin1b (Cntn1b), which is an immunoglobulin (Ig)‐superfamily domain‐containing membrane‐anchored protein. The ro mutant had a deletion in the cntn1b gene that introduced a premature stop codon. Furthermore, cntn1b mutants generated by the CRISPR/Cas9 system and trans‐heterozygotes of the CRISPR mutant allele and ro had abnormal swimming behavior, indicating that the cntn1b gene was responsible for the ro‐ mutant phenotype. We also established zebrafish cntn1a and cntn1b mutants by transcription activator‐like effector nucleases (TALENs). Zebrafish cntn1b but not cntn1a mutants showed abnormal swimming behaviors similar to those in the ro mutant, suggesting that Cntn1b plays a conserved role in the formation or function of the neural circuits that control swimming in teleosts. Although Cntn1 ‐deficient mice have abnormal cerebellar neural circuitry, there was no apparent histological abnormality in the cerebellum of medaka or zebrafish cntn1b mutants. The medaka cntn1b mutants had defective optokinetic response (OKR) adaptation and abnormal rheotaxis (body positioning relative to water flow). Medaka and zebrafish cntn1b mutants are effective models for studying the neural circuits involved in motor learning and motor coordination. Abstract : Cntn1b is required for controlling head position in rheotaxis. (A) Experimental setup for analyzing swimming behavior. (B) Medaka cntn1b (ro) mutants cannot keep a stereotaxic position while swimming into the water flow.